Содержание понятия «духовная жизнь»: опыт анализа - Норманская, Ю.В. (Культура народов Причерноморья, 2014)
Статья посвящена анализу определений понятия «духовная жизнь», данных современными
российскими исследователями – философами, социологами, культурологами, историками. Основное
внимание акцентируется на сходстве и различии взглядов на данную проблему представителей разных
сфер гуманитарной науки. Показано, что многообразие авторских трактовок духовной жизни может
быть объяснено различными мировоззренческими позициями ученых, а также спецификой решаемых
ими исследовательских задач. Стаття присвячена аналізу визначень поняття «духовне життя», даних сучасними
російськими дослідниками – філософами, соціологами, культурологами, істориками. Основна увага
акцентується на схожості і відмінності поглядів на дану проблему представників різних сфер
гуманітарної науки. Показано, що різноманіття авторських трактувань духовного життя може бути
пояснено різними світоглядними позиціями вчених, а також специфікою вирішуваних ними
дослідницьких завдань. The word «spirituality», «spiritual life» have become part of our lives. They appear in the religious
and secular literature, in the media, in research, in everyday communication. This article analyzes the
definitions of «spiritual life», these modern Russian scientists – philosophers, sociologists, historians. The main
attention is focused on the similarities and differences of views on the issue of representatives of different areas
of the humanities. For example, reflections I. Artemova different train of thought from L. Kertman. If L. Kertman
defines culture through spiritual life, I. Artemova prefers to differentiate these concepts. Thesis researcher of the
manifestation of the spiritual culture of moral consciousness and finds confirmation in other studies. Thus, there
are more recent studies on the moral consciousness as a phenomenon of spiritual life. Inalienability of religion
in the structure of the spiritual life stresses and Russian philosopher A. Trishin.
Thus, the authors emphasize the multidimensional nature of the spiritual life, confirming the generally accepted
thesis that the spiritual life is holistic relatively independent system, and has a complex structure and
characteristics. The variety of interpretations of copyright spiritual life can be explained by the different
philosophical positions of scientists, as well as the specifics of their research problems solved. For the further development of this problem we study seems appropriate interpretations of the concept
«spiritual» life scientists in relation to other cultural traditions, as well as an appeal to the religious writings of
the authors, with different religious affiliation.